(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pramono H, Mariana A, Ryandini D, Sudiana E. 2021. Short Communication: Diversity of cellulolytic bacteria isolated from coastal mangrove sediment in Logending Beach, Kebumen, Indonesia. Biodiversitas 22: 1869-1878. Bacteria from mangrove sediments have the potential to produce active enzymes and metabolites needed in the industry. Mangrove ecosystems in various parts of Indonesia have been explored as sources of bacteria. However, the mangrove ecosystems in Logending Beach, Kebumen District, Indonesia are still unexplored. This study aims to determine the diversity of cellulolytic bacteria using the 16S rRNA gene. Ninety-nine bacteria were isolated from Logending coastal mangrove sediments. Most of them (87.87%) had a cellulolytic activity, with the cellulolytic index values ranged from 0.25–13.96. The LG2 isolate had the highest cellulolytic activity (13.96). Molecular characterization of the LG2 isolate based on the 16S rRNA gene showed that it was similar to the Fictibacillus nanhaiensis strain JSM 082006. This result is new information on cellulolytic bacteria and might be used as a future source of cellulolytic enzymes.